KNOWLEDGE AND CULTURE IN THE EARLY DUTCH REPUBLIC ([S.l.])
1 online resource
Keywords: The Dutch Republic around 1600 was a laboratory of the Scientific Revolution of the seventeenth century. Here conditions were favourable for the development of new ways of knowing nature and the natural philosopher Isaac Beeckman, who was born in Middelburg in 1588, was a seminal figure in this context. He laid the groundwork for the strictly mechanical philosophy that is at the heart of the new science. Descartes and others could build on what they learned, directly or indirectly, from Beeckman. As previous studies have mainly dealt with the scientific content of Beeckman's thinking, this volume also explores the wider social, scientific and cultural context of his work. Beeckman was both a craftsman and a scholar and fruitfully combined artisanal ways of knowing with international scholarly traditions. Beeckman's extensive private notebook offers a unique perspective on the cultures of knowledge that emerged in this crucial period in intellectual history.